Research on motor neuron diseases konzo and neurolathyrism: trends from 1990 to 2010. - Delphin Diasolua Ngudi (Public Library of Science (PLoS), 2012)
Konzo (caused by consumption of improperly processed cassava, Manihot esculenta) and neurolathyrism (caused by prolonged overconsumption of grass pea, Lathyrus sativus) are two distinct non-infectious upper motor neurone diseases with identical clinical symptoms of spastic paraparesis of the legs. They affect many thousands of people among the poor in the remote rural areas in the central and southern parts of Africa afflicting them with konzo in Ethiopia and in the Indian sub-continent with neurolathyrism. Both diseases are toxico-nutritional problems due to monotonous consumption of starchy cassava roots or protein-rich grass pea seeds as a staple, especially during drought and famine periods. Both foods contain toxic metabolites (cyanogenic glycosides in cassava and the neuro-excitatory amino acid β-ODAP in grass pea) that are blamed for theses diseases. The etiology is also linked to the deficiency in the essential sulfur amino acids that protect against oxidative stress. The two diseases are not considered reportable by the World Health Organization (WHO) and only estimated numbers can be found. This paper analyzes research performance and determines scientific interest in konzo and neurolathyrism. A literature search of over 21 years (from 1990 to 2010) shows that in terms of scientific publications there is little interest in these neglected motorneurone diseases konzo and neurolathyrism that paralyze the legs. Comparison is made with HTLV-1/TSP, an infectious disease occurring mainly in Latin America of which the clinical manifestation is similar to konzo and neurolathyrism and requires a differential diagnosis. Our findings emphasize the multidisciplinary nature of studies on these neglected diseases, which however have not really captured the attention of decision makers and project planners, especially when compared with the infectious HTLV-1/TSP. Konzo and neurolathyrism can be prevented by a balanced diet.